The Performance of Hydraulic Fractures Partially Filled with Compressible Proppant - Bortolan Neto, L.; Khanna, A. (Australian journal of multi-disciplinary engineering, 2013)
Mechanical response of a proppant pack to confining stresses significantly influences the aperture of highly conductive artificial or natural fracture channels and, to some extent, determines the efficiency of hydraulic stimulations. This paper presents a simplified mathematical model of a crack partially filled with compressible proppant subject to remote compressive stress and a computational approach for evaluating the productivity rate of hydraulically stimulated wells. The conducted case studies confirm that the proppant pack distribution and compressibility have a significant impact on well productivity. Furthermore, it is suggested that under certain conditions, for example, relatively low confining stresses, the partially propped fractures can lead to higher well production rate than fractures fully filled with proppant. The benefit of reducing proppant pack compressibility for improving the performance of wells with partially propped fractures is also verified.